Comparative Nutritional Status of Infants with Exclusive Breastfeeding and Formula Milk at Puskesmas Dadok Tunggul Hitam, Padang City - Hayu, Ramah; Ilona, Sandra; Fransisca, Dewi (PT. Riset Press International, 2025)
Exclusive breastfeeding is crucial for optimal growth and development of infants, as it provides essential nutrition and immunity. However, in Padang City, the coverage of exclusive breastfeeding varies significantly. Data from 2021 shows that the highest coverage is at Bungus Health Center, with 86.9%, while the lowest is at Dadok Tunggul Hitam Health Center, at only 25.67%. This discrepancy raises concerns about the nutritional status of infants who do not receive exclusive breastfeeding, as nutritional status is a key indicator of overall health and development. This study investigates the differences in nutritional status between infants who receive exclusive breastfeeding and those given formula milk at Dadok Tunggul Hitam Health Center. This descriptive-analytic research employs a cross-sectional approach with 96 infants over 6 months old. Data was collected through interviews using questionnaires and analyzed with T-test. The results show that the average nutritional status of infants receiving exclusive breastfeeding is -2.23, while for those receiving formula milk, it is -2.04. This significant difference indicates that infants who receive exclusive breastfeeding have better nutritional status. The study recommends that healthcare workers, especially midwives at the health centre, be more proactive in providing information about the benefits of exclusive breastfeeding to improve infant nutritional status, particularly in areas with low coverage.